Analysis of Maths Learning Activities Developed By Pre-service Teachers in Terms of the Components of Content, Purpose, Application Methods - Çağla Toprak, Işıkhan Uğurel, Gökçe Tuncer , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2014)
Today- when the influence of the alteration movement done in order to keep up with the age of the educational system is still continuing- the importance of teachers in students’ learning and achieving what is expected from the education system has been stated by the studies conducted (Hazır & Bıkmaz, 2006). Teachers own a critical role in the stage of both preparing teaching materials and using them (Stein & Smith, 1998b; Swan, 2007). When the existing curriculums –in particular, maths and geometry cirriculums- are analyzed, it can be observed that activities are the most significant teaching materials (Bozkurt, 2012). In fact, it is possible to characterize the existing curriculums as activity-based ones (Report of Workshop Examining Content of Primary School Curriculums According to Branches, 2010; Epö, 2005). Therefore, what sort of learning activities there are, what qualities they need to have, how to design and apply them are topics that must be elaborated (Uğurel et al., 2010). At this point, our study to increase the skills of pre-service teachers during the process of developing activities was conducted with 27 pre-service teachers -19 girls 8 boys- studying in the 4th year in Mathematics Education Department at a state university in the Aegean Region. The activity designs the pre-service teachers developed considering the patterns given after a series of practice were analyzed in documents in terms of the aim of design and the form of practice. As a result of the studies, it is observed that pre-service teachers deal with the topics from the maths curriculum and these topics are of different grade levels. The result of the examination named as target component suggests that activities developed aim firstly at providing learning and this is followed by reinforcing the concepts already learned. It is stated that pre-service teachers prefer mostly small group (cooperative) studies in the activities they develop.